2015
DOI: 10.1177/1535370215588924
|View full text |Cite
|
Sign up to set email alerts
|

Recent discoveries concerning the involvement of transcription factors from the Grainyhead-like family in cancer

Abstract: The Grainyhead-like (GRHL) family of transcription factors has three mammalian members, which are currently termed Grainyhead-like 1 (GRHL1), Grainyhead-like 2 (GRHL2), and Grainyhead-like 3 (GRHL3). These factors adopt a DNA-binding immunoglobulin fold homologous to the DNA-binding domain of key tumor suppressor p53. Their patterns of expression are tissue and developmentally specific. Earlier studies of the GRHL proteins focused on their functions in mammalian development. In recent years, these factors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 53 publications
(131 reference statements)
0
68
0
Order By: Relevance
“…Previously, we reported that GRHL2 suppresses the oncogenic EMT, i.e., promotes MET (1517). The loss of GRHL2 expression is associated with aggressive, metastatic breast tumor types that contain an unusually large fraction of EMT-like subpopulations, and in the cancer stem cell-like subpopulation of tumors resulting from EMT and/or drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that GRHL2 suppresses the oncogenic EMT, i.e., promotes MET (1517). The loss of GRHL2 expression is associated with aggressive, metastatic breast tumor types that contain an unusually large fraction of EMT-like subpopulations, and in the cancer stem cell-like subpopulation of tumors resulting from EMT and/or drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The Claudin-low subtype of breast cancer expresses low levels of GRHL2, E-cadherin and claudin 4, is highly metastatic, and GRHL2 expression positively correlates with distant metastasis-free survival (Cieply et al, 2012(Cieply et al, , 2013Mlacki et al, 2015). GRHL2 acts as a suppressor of EMT in breast cancer cell lines and can directly repress the EMT-promoting TF ZEB1 (Cieply et al, 2012(Cieply et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Similar processes have been implicated in cancer metastasis, where transformed cells spread from a primary tumor in an EMT-like process, and relocate to additional sites in the body by reverting back to a mesenchymal cell fate (Kalluri and Weinberg 2009;Thiery et al 2009). Misexpression of each of the mammalian Grh-family members has been associated with a range of epithelium-derived cancers (Mlacki et al 2015). Given the function of Grh-family members in driving epithelial cell fate, it was predicted that these proteins might function as tumor suppressors by suppressing the EMT and metastasis.…”
mentioning
confidence: 99%